Choice of Alternatives for Completing Work Tip 182 70 kV GI Namlea–Namrole GI Transmission Project Using Analytical Methods Hierarchy Process (AHP) - Firman Syarip; Machsus Machsus (Universitas Mercu Buana, 2026)
Objectives: This study aims to identify the criteria that must be considered in selecting alternative solution for the Tower Intersection Point (TIP) 182 issue on Buru Island, Maluku. The problem emerged after a landslide at the foundation of TIP 182 caused the leg C foundation to sink and the surrounding ground to crack. The research seek to analyze the best alternative solution using the Analytical Hierarchy Process (AHP) method and evaluate the sensitivity of the selected criteria to ensure the robustness of the chosen alternative.Methodology: Data were collected through Focus Group Discussion (FGD) to formulate relevant criteria and alternative solutions, as well as questionnaires to determine the weight of each criterion. The Analytival Hierarchy Process (AHP) was employed to prioritize and rnk the alternatives based on the established criteria. Sensitivity analysis was conducted to assess the stability of the selected alternative under change in criteria weighting.Findings: The FGD identified three alternatives; relocation of the TIP 182, redesign of TIP 183 and cutting slope. Five main criteria were analyzed in depth; technical aspects, resources, cost, duration and risk. The AHP results indicate that the redesign TIP 183 alternatives is the most optimal solution for addressing the problem at TIP 182 on Buru Island. Sensitivity analysis further confirms that variations in the weights of the technical, resources, cost, duration and risk criteria do not significantly alter the ranking position of the redesign TIP 183 alternative as the most superior option.Conclusion: The study concludes that redesign TIP 183 is the most appropriate and robust alternative solution for resolving the TIP 182 issue. The application of AHP provides a structured and objective decision-making framework that supports effective project completion and practical implementation on the field, while also offering a foundation for future related research.